Analysis of M&A activities of foreign investors in Vietnam in the global economic crisis (2008-2012) = Phân Tích hoạt động mua bán sát nhập của các nhà đầu tư nước ngoài tại Việt Nam trong giai đoạn khủng hoảng kinh tế toàn cầu (2008-2012) - Bùi, Việt Nhật Thanh (2021)
The thesis will make clearer the situation of cross-border merger and acquisition activities in Vietnam in the period of 2008-2012. The term of M&A is defined and the point of regional and international views toward the definition of M&A were also added. The trend of the general M&A transaction in Vietnam and inbound ones were analysed and the study on its impacts would be carried out. The factors that operated the M&A activities were also introduced in order to release the analysis and recommendations for the government and domestic enterprise when they faced with the dozens of foreign-related M&A.